PENGEMBANGAN TRANSDERMAL DRUG DELIVERY SYSTEM (TDDS) PATCH METHYLDOPA SEBAGAI ANTIHIPERTENSI PADA KEHAMILAN - Mayna, Mayna; Noval, Noval; Khairunnisa, Aisya Fitri; Octaviani, Olivia; Wilujeng, Wilujeng (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Hypertension in pregnancy including chronic hypertension with or without pre-eclampsia, gestational hypertension increases maternal and infant mortality significantly. The treatment for hypertension in pregnancy is the administration of methyldopa. Methyldopa transdermal patch is made by mixing the polymer first and then adding the active substance, namely methyldopa drug. It is intended that the polymer becomes an outer layer that controls the release of the drug. The resulting transdermal patch formulation was then evaluated, including organoleptic test, pH test, weight uniformity test, patch thickness test, folding resistance test, moisture test and penetration test using Franz diffusion cell. SPSS statistical data analysis. The penetration rate results showed F1 with 832.16 µg/cm2, F4 with 767.95 µg/cm2, F2 with 2819 µg/cm2 and F3 with 275.38 µg/cm2 all formulas have met the requirements. Based on the results of physical characteristics evaluation research, all formulas have met the requirements. The results of the in vitro evaluation of the methyldopa patch transdermal penetration test found that the difference in concentration in each formula had no significant effect on the penetration test. Based on physical evaluation parameters and in vitro penetration tests, the most optimal formula is F4 with the ratio of HPMC and ethyl cellulose (300:100) seen by fulfilling all physical characteristic evaluation tests and having a constant percent of cumulative amount to rise.